Analisis Peran Manajemen Risiko dalam Menjaga Stabilitas Keuangan Syariah di Tengah Ketidakpastian Ekonomi Global - Naqi, Nadiyatun (Maliki Interdisciplinary Journal, 2025)
Global economic uncertainty triggered by geopolitical conflict, health crisis, and market volatility demands sharia financial institutions to strengthen their risk management systems. This article aims to examine the strategic role of risk management in maintaining the stability of sharia finance with an approach based on Islamic principles, such as justice, transparency, and social responsibility. Share-based financing mechanisms such as mudharabah and musyarakah are considered effective in encouraging fair risk distribution and strengthening accountability. In addition, the synergy between the conventional risk management system and the supervision of the Syariah Supervisory Board (DPS) is a key element in creating institutional resilience. With the implementation of an integrated risk management system and in accordance with sharia values, sharia financial institutions are expected to be able to respond to global challenges in a more adaptive and sustainable way.